Ultra-high performance liquid chromatography Q-Orbitrap MS/MS-based profiling and quantification of limonoids in Meliaceae plants - Mulani, Fayaj A.; Nandikol, Sharvani S.; Kajjihundi, Jagadeesh S.; Pathappa, Niranjana; Puttappa, Sharanappa; Thulasiram, V. Hirekodathakallu (Analytical and Bioanalytical Chemistry, 2022)
Meliaceae plants have been extensively used in agriculture, folklore, and traditional medicine. They are the major storehouses for structurally diverse limonoids (meliacins) possessing various bioactivities like antifeedant, insecticidal, antimicrobial, etc. However accurate detection of these tetranortriterpenes from the vast pool of metabolites in plant tissue extracts or biological sample is a crucial challenge. Though the mass spectrum (MS) provides the molecular mass and the corresponding elemental composition, it cannot be relied precisely. The exact identification of a specific metabolite demands the MS/MS spectrum containing the signature product ions. In the present study, we have developed the UHPLC Q-Orbitrap-based method for identification, quantification, and characterization of limonoids in different plant tissue extracts requiring minimum plant material. Using this method, we carried out the limonoid profiling in different tissue extracts of sixteen Meliaceae plants and the identification of limonoids was performed by comparing the retention time (RT), ESI-(+)-MS spectrum, and HCD-MS/MS of the purified fifteen limonoids used as reference standards. Our results revealed that early intermediates of the limonoid biosynthetic pathway such as azadiradione, epoxyazadiradione, and gedunin occurred more commonly in Meliaceae plants. The MS/MS spectrum library of the fifteen limonoids generated in this study can be utilized for identification of these limonoids in other plant tissue extracts, botanical fertilizers, agrochemical formulations, and bio pesticides.
Keywords: LC-HRMS; LC-MS/MS; Limonoids; Meliaceae; Natural product; Quantification